The Preservation of the Gjøa (Polar Record, 1940)
It is reported in Polar-drboken for 1939 that Roald Amundsen's ship used during the North-West Passage Expedition has been saved from destruction. The Town Council of San Francisco has granted $12,500 for its restoration at the Golden Gate. When the first part of this work is completed a house will be built over the ship, as has been done with the Fram at Oslo.